Intimate partner violence among pregnant women in Kenya: forms, perpetrators and associations - Mariella Stiller; Till Bärnighausen; Michael Lowery Wilson (My University, 2022)
Background: Intimate Partner violence (IPV) among pregnant women is a signifcant problem of public health importance. Nevertheless, there are relatively few studies which have examined the phenomenon in sub-Saharan settings. The aim of this study was to provide an overview of the prevalence, perpetrators, and associated factors of IPV during pregnancy in Kenya. Methods: We were making use of the 2014 Kenyan Demographic and Health Survey (KDHS) data and included women and girls of reproductive age (15–49 years) who have ever been pregnant (n = 4331). A weighted sample of respondents who have experienced violence during pregnancy (n = 397) were selected for further bivariate and multivariable logistic regression analyses in order to examine the association between IPV and socio-demographic factors. Results: The prevalence of violence among pregnant women in Kenya was 9.2%, perpetrated mostly by the current husband or partner (47.6%), followed by the former husband or partner (31.5%). Physical violence was the most common (78.6%), followed by emotional (67.8%) and sexual (34.8%). Having one or two children (aOR = 0.68; CI = 0.53−0.88), having secondary or higher education (aOR = 0.53; CI = 0.40−0.69) and being 18 years and above at frst cohabitation (aOR = 0.75; CI = 0.60−0.94) and at sexual debut (aOR = 0.65; CI = 0.53−0.80) were signifcantly associated with fewer reports of violence during pregnancy. Pregnant women who were divorced, separated or widowed (aOR = 1.91; CI = 1.47−2.47), who were employed (aOR = 1.34; CI = 1.06−1.70), who had witnessed their fathers beat their mothers (aOR = 1.59; CI = 1.28−1.97) and who had primary education (aOR = 1.53; CI = 1.11−2.14) were signifcantly more likely to experience violence. Conclusions: To prevent violence among pregnant women in Kenya, training health care providers should go hand in hand with interventions sensitising and mobilising community members, both addressing the socio-demographic drivers of IPV during pregnancy and directing a particular attention to the most vulnerable ones.
Keywords: Women’s health, Intimate partner violence, Pregnancy, Kenya, Associations, Demographic and health survey